LOCAL CURRENCIES SUPPORTING THE IMPLEMENTATION OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT IN EUROPE - Patrycja Konieczna (Copernican Journal of Finance & Accounting, 2022)
Local currencies represent an alternative to fiat money. They contribute to the development of local communities, primarily by supporting small and medium-sized enterprises, which remain fundamental for the economy of every European country. The purpose of the study is to identify both ways and methods focused on supporting the implementation of the concept of sustainable development by the selected local currencies in the area of Europe, analysed in the years 1932–2020. The paper takes the form a descriptive analysis based on the studies covering Polish, Czech, Dutch, German and English source literature as well as the Community Currencies in Action (CCIA) publications, websites of the analysed local currencies and other studies in the field of financial law. The method of comparative analysis was used to examine the similarities and differences in supporting the implementation of the concept of sustainable development. The basic conclusion formulated after conducting the research is the fact that each local currency does support sustainable development in an indirect way. In addition, certain local currencies can be identified, in the case of which the support of sustainable development is the essence of their functioning. The effectiveness of the impact exerted by local currencies on sustainable development depends on the involvement of the creators of these currency systems and the specificity of the existing conditions. The ability to establish partnerships between non-governmental organisations, business entities and public administration may also play a significant role.